A Chinese classical prescription Maimendong decoction in treatment of pulmonary fibrosis: an overview - Lao, Qiurong; Wang, Xianbin; Zhu, Guangqing; Yuan, Haochen; Ma, Ting; Wang, Ning (Frontiers in Pharmacology, 2024)
Pulmonary fibrosis (PF) is a chronic and progressive disease characterized by fibrosis and interstitial pneumonia. It has similar clinical symptoms to ＂Fei Bi＂ and ＂Fei Wei＂as described in the traditional Chinese medicine (TCM) classic Jingui Yaolue written by Zhang Zhongjing in the Han Dynasty. This study explored the potential of Maimendong Decoction (MMDD). MMDD consists of Ophiopogon japonicus (L.f) (ophiopogonis), Pinellia ternata (Thunb.) Breit. (pinellia), Panax ginseng C. A. Mey. (ginseng), Glycyrrhiza uralensis Fisch. (glycyrrhiza), Zizi phus jujuba Mill. (jujuba), and Oryza sativa L. (oryza sativa), with the function of nourishing the lung and stomach, and reducing the effect of reverse qi. It has been used clinically for over two thousand years to treat conditions like "Fei Bi" and "Fei Wei". Previous research suggests that MMDD and its individual herbal extracts have anti-fibrotic effects. The main focus of MMDD in treating PF is to reduce inflammatory cytokines, inhibit pro-fibrotic factors and oxidative stress, promote differentiation and homing of bone marrow mesenchymal stem cells, and enhance cell autophagy activity. This review summarized the clinical applications, mechanisms, and pharmacological effects of MMDD in treating PF based on existing clinical applications and experimental research. It also discussed current issues and prospects, aiming to provide a reference for further research on the mechanism of PF, drug development, and clinical trials.